A finance leader's guide to automating analytics - Rasheed, Jawwad (O'Reilly Media, Inc., 2023)
Today's finance leaders have evolved from their role as technical experts in accounting, tax, and governmental regulations to become strategic and invaluable members of executive leadership teams. In this report, author Jawwad Rasheed demonstrates how finance leaders now rely on data, analytics, and automation to build more adaptable and resilient organizations. Current economic headwinds, persistent inflation, supply chain disruptions, and geopolitical instabilities have presented challenges that companies have never faced before. This book demonstrates how finance leaders in smart organizations have discovered that the key to unlocking a company's potential is democratizing analytics. You'll learn how companies have applied analytics automation to spur decision-making in FP&A, tax, audit, accounting, ESG, and other processes.
Keywords: Visual analytics; Financial executives; Financial risk management; Analyse visuelle; Finances; Gestion du risque